Strategic co-funding in informal finance market: Evidence from China - Jianwen Li; Xiaofan Zhang; Jinyan Hu (Journal of Applied Economics, 2021)
Information asymmetry in the anonymous informal finance market drives the lenders to screen the borrowers by disclosed information. Using data from a powerful online peer-to-peer lending platform, we study the effects of formal financing records on successful funding and default outcomes in the informal finance market. We find that lenders are more likely to fund borrowers with formal financing records. Borrowers with formal credit are more likely to repay the loans entirely. Co-funding with the formal financial sector is strategic, corresponding to lower default risk. Moreover, without historical success records or with a low-income level, borrowers can use the formal credit signals to mitigate information asymmetry and improve the funding probability. These results are obtained after controlling for loan-level and borrower-level information, city-by-year-month, and day-of-week fixed effects. Several tests show our findings are unlikely to be an unintentional byproduct of the formal financial signals.
Keywords: 330; co-funding; informal finance; Information asymmetry; peer-to-peer lending